A Clinical Review of the Treatment of Catatonia - Sienaert, Pascal; Dhossche, Dirk M.; Vancampfort, Davy; De Hert, Marc; Gazdag, Gábor (Frontiers in Psychiatry, 2014)
Catatonia is a severe motor syndrome with an estimated prevalence among psychiatric inpatients of about 10%. At times, it is life-threatening especially in its malignant form when complicated by fever and autonomic disturbances. Catatonia can accompany many different psychiatric illnesses and somatic diseases. In order to recognize the catatonic syndrome, apart from thorough and repeated observation, a clinical examination is needed. A screening instrument, such as the Bush-Francis Catatonia Rating Scale, can guide the clinician through the neuropsychiatric examination. Although severe and life-threatening, catatonia has a good prognosis. Research on the treatment of catatonia is scarce, but there is overwhelming clinical evidence of the efficacy of benzodiazepines, such as lorazepam, and electroconvulsive therapy.